Genetic characteristics of waterfowl-origin H5N6 highly pathogenic avian influenza viruses and their pathogenesis in ducks and chickens - He, Zhuoliang; Wang, Xia; Lin, Yu; Feng, Siyu; Huang, Xinyu; Zhao, Luxiang; Zhang, Junsheng; Ding, Yangbao; Li, Weiqiang; Yuan, Runyu; Jiao, Peirong (Frontiers in Microbiology, 2023)
Waterfowl, such as ducks, are natural hosts for avian influenza viruses (AIVs) and act as a bridge for transmitting the virus to humans or susceptible chickens. Since 2013, chickens and ducks have been threatened by waterfowl-origin H5N6 subtype AIVs in China. Therefore, it is necessary to investigate the genetic evolution, transmission, and pathogenicity of these viruses. In this study, we determined the genetic characteristics, transmission, and pathogenicity of waterfowl-origin H5N6 viruses in southern China. The hemagglutinin (HA) genes of H5N6 viruses were classified into the MIX-like branch of clade 2.3.4.4h. The neuraminidase (NA) genes belonged to the Eurasian lineage. The PB1 genes were classified into MIX-like and VN 2014-like branches. The remaining five genes were clustered into the MIX-like branch. Therefore, these viruses belonged to different genotypes. The cleavage site of the HA proteins of these viruses was RERRRKR/G, a molecular characteristic of the H5 highly pathogenic AIV. The NA stalk of all H5N6 viruses contained 11 amino acid deletions at residues 58–68. All viruses contained 627E and 701D in the PB2 proteins, which were molecular characteristics of typical bird AIVs. Furthermore, this study showed that Q135 and S23 viruses could replicate systematically in chickens and ducks. They did not cause death in ducks but induced mild clinical signs in them. All the infected chickens showed severe clinical signs and died. These viruses were shed from the digestive and respiratory tracts and transmitted horizontally in chickens and ducks. Our results provide valuable information for preventing H5N6 avian influenza outbreaks.